Smart in city performance: More to practical life than hardware and software. Issue 1 (17th November 2022) - Hatem, Faten
Abstract: Visions of Smart cities claim to offer better liveability and sustainability through information and communication technology. This study promotes the importance of focussing on spatial aspects and affective factors that impact smart urbanism. It seeks better to inform city governance, spatial planning, and policymaking to focus on what Smart does and what it can achieve for cities in terms of performance rather than on using the notion for prestige purposes. Also, the study recognises the importance of establishing a new meaning for urban progress by moving beyond improving the city's basic services to enhance the actual human experience, which is essential for developing authentic smart cities. The topic presents four overlooked areas: the efficiency paradox, the social aspect, connectedness with nature, and utilising untapped resources. The argument does not invite exploring these themes in silos; it collectively examines smart cities in performance, arguing that there is more to the practical life of smart cities than software and hardware inventions. The research uses a case study approach, presenting Milton Keynes as a living example to learn from while engaging with various methods for data collection, including multi‐disciplinary semi‐structured interviews, field observations, and data mining.